2021
DOI: 10.3390/coatings11091035
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stem Cells in Augmenting Dental Implant Osseointegration: A Systematic Review

Abstract: Dental implants are a widely used treatment modality for oral rehabilitation. Implant failures can be a result of many factors, with poor osseointegration being the main culprit. The present systematic review aimed to assess the effect of stem cells on the osseointegration of dental implants. An electronic search of the MEDLINE, LILACS, and EMBASE databases was conducted. We examined quantitative preclinical studies that reported on the effect of mesenchymal stem cells on bone healing after implant insertion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…20 This phenomenon can be correlated with the relationship between LLLT stimulation and the tissue stem cells reacting to it, inducing the new formation and healing of the peri-implant soft tissues and the periimplant bone. 32 Similar results were found in the studies by Torkzaban et al 22 and Bittencourt Lobato et al, 24 even though the observed differences were not statistically significant. The pooled result of all the studies included in the meta-analysis showed a positive effect of the PBM therapy on dental implant stability in contrast to the other systematic review results.…”
Section: Discussionsupporting
confidence: 82%
“…20 This phenomenon can be correlated with the relationship between LLLT stimulation and the tissue stem cells reacting to it, inducing the new formation and healing of the peri-implant soft tissues and the periimplant bone. 32 Similar results were found in the studies by Torkzaban et al 22 and Bittencourt Lobato et al, 24 even though the observed differences were not statistically significant. The pooled result of all the studies included in the meta-analysis showed a positive effect of the PBM therapy on dental implant stability in contrast to the other systematic review results.…”
Section: Discussionsupporting
confidence: 82%
“…Dental implants are commonly used in dentistry, orthopedic surgery and other specialties that work on human skeleton ( Sayed et al, 2021 ). Biocompatibility properties of these materials have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, modern techniques of stem cell stimulation and bone neo-apposition with grafts are progressing; they also offer good opportunities in implant re-osseointegration. [ 8 ] To improve the stability and osseointegrations of implants, the dentistry industry uses a variety of scaffolds and growth factors [ 8 , 9 ]. Bioactive-molecule-loaded scaffolds show a main role in the promotion of stability and osseointegration in implants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] To improve the stability and osseointegrations of implants, the dentistry industry uses a variety of scaffolds and growth factors [ 8 , 9 ]. Bioactive-molecule-loaded scaffolds show a main role in the promotion of stability and osseointegration in implants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%